Impact of the Russian trade bans on Lithuanian pork sector - Nelė Jurkėnaitė; Ivan Djuric (Management Theory and Studies for Rural Business and Infrastructure Development, 2018)
Over the last decade, Lithuanian pork sector faced dramatic changes, where trade relations with Russia had an important role. The research problem is defined as follows: how does the trade ban of Russia, imposed towards live pigs and pork originating from Lithuania, affect price changes on domestic Lithuanian pork market? The research aims at estimating the effects of the trade ban caused by the outbreak of the swine fever in Lithuania and providing proposals on situation development. The aim is achieved by analysing the transmission of price changes between Lithuanian and Russian pork markets by using the ARDL model. The results indicate a significant decrease in transmission of price changes, both in short- and long-run, from Lithuanian pig prices towards Russian domestic prices during the `2011 ban' regime and further worsening of the situation during `2014 ban' period that was mainly caused by the isolation of the Russian market and lack of export diversification strategy from the Lithuanian side. In Lithuania, high price volatility was not typical during the bans, while negative effects on welfare of farmers were evidenced by reduced trade volumes, which could be improved by biosafety and disease spread reducing measures, reassessing trade regulations and partners' network.
Keywords: C22; Q11; 330; agriculture; trade ban; export; supply chain; pork